2022
DOI: 10.3390/ijms23179951
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Suitability of 3D Bioprinted Samples for Experimental Radiotherapy: A Pilot Study

Abstract: Radiotherapy is an important component in the treatment of lung cancer, one of the most common cancers worldwide, frequently resulting in death within only a few years of diagnosis. In order to evaluate new therapeutic approaches and compare their efficiency with regard to tumour control at a pre-clinical stage, it is important to develop standardized samples which can serve as inter-institutional outcome controls, independent of differences in local technical parameters or specific techniques. Recent developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Three-dimensional organ models have developed as an alternative approach to conventional animal experiments, which are composed of human cells and, at the same time, may help to reduce the number of animal experiments [ 33 ]. Bioprinting is one of the most promising technologies for producing disease models for oncology research and can be used to develop anticancer substances and optimize irradiation procedures [ 20 , 34 ]. Compared to other techniques for the generation of 3D cultures, such as organoid formation, bioprinting has the advantage of allowing for the computer-based design of 3D objects with a predefined structure [ 18 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional organ models have developed as an alternative approach to conventional animal experiments, which are composed of human cells and, at the same time, may help to reduce the number of animal experiments [ 33 ]. Bioprinting is one of the most promising technologies for producing disease models for oncology research and can be used to develop anticancer substances and optimize irradiation procedures [ 20 , 34 ]. Compared to other techniques for the generation of 3D cultures, such as organoid formation, bioprinting has the advantage of allowing for the computer-based design of 3D objects with a predefined structure [ 18 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…3D printing has gained extensive utilization in producing highly reproducible 3D environments with precise structures for 3D cell growth. ,, In 3D bioprinting, hydrogel ink fluidity is crucial. For this purpose, gelatin is usually mixed with alginate to initiate gelation prior to bioprinting. , Previous studies have shown that an ink consisting of ∼2% (w/v) alginate and ∼3% (w/v) gelatin has good elasticity and loss modulus that are favorable for extrusion printing and cell viability. , These concentrations also ensure the robust stability of the printed products for cell culture process Figure a shows a hydrogel ink prepared using this alginate/gelatin concentration following loading into a 3D printing cartridge.…”
Section: Results and Discussionmentioning
confidence: 99%
“…44,45 Previous studies have shown that an ink consisting of ∼2% (w/v) alginate and ∼3% (w/v) gelatin has good elasticity and loss modulus that are favorable for extrusion printing and cell viability. 39,46 These concentrations also ensure the robust stability of the printed products for cell culture process. 39 Figure 2a shows a hydrogel ink prepared using this alginate/gelatin concentration following loading into a 3D printing cartridge.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…5 × 10 mm sample generated in a 3D bioprinting technique from malignant tumor cells. The bioprinting technique has been previously described [ 29 ]. 3D bioprinted material can be reproducibly custom shaped during the printing process, to fit the requirements of each individual experiment.…”
Section: Resultsmentioning
confidence: 99%
“…In August 2016, we conducted a first MRT feasibility study at the monochromatic beamline P07. Based on the results of that experiment and subsequent studies at the monochromatic beamline P21.2 [ 29 ], we decided to develop a dedicated setup for biomedical high dose rate irradiation studies at the new white beam beamline P61A which was, at that time, designed and constructed under the leadership of the Helmholtz Centre Geesthacht (now HEREON). The safety tests for this new beamline were passed in November 2020.…”
Section: Introductionmentioning
confidence: 99%